From the Hydroclimatic Disaster to the Forced (Re)construction: Case Study of the Akatani Watershed in Japan - Mélody Dumont; Gilles Arnaud-Fassetta; Christopher Gomez; Candide Lissak; Vincent Viel (Proceedings)
On 5–6 July 2017 (J17), an unusual series of rainfalls induced a concentration of precipitations in Northern Kyushu, Japan, reaching 516 mm in 24 h in Asakura City, a first in its history since the beginning of observation in 1976. This triggered unprecedented hydro-meteorological hazards (landslides, debris flows, and floods) in forested mountainous areas, such as in the Akatani watershed, where the estimated discharge reached 520 m3/s at its outflow. It induced numerous deaths, structural damages, destruction of river channels, and deposition of sediment in flood plains. If smaller-scale hazards have usually driven authorities to build protection systems in the watershed, the J17 crisis called for a full remodeling of it, interrupting waterways and reshaping slope shapes and structures. Considering the means deployed by the central government for this reconstruction, the J17 event triggered a full “re-construction” of rivers, modifying the hydrosystem’s functioning at the watershed scale. Thus, our objective is to show that after the relative stability of Akatani watershed’s hydrosystem over 75 y, the exceptionality of the J17 crisis forced us to rethink the watershed’s organization, using this event as the reference for post-disaster reconstruction. The research relies on field surveys in 2019 and 2022, interviews of officials, and GIS analysis based on historical aerial photograph interpretation and geospatial data. It revealed that (a) the geometry of post-disaster channels was completely redesigned to match a new reference and (b) sediment control structures were multiplied to restructure slopes, breaking the slope angles into subwatersheds. The Akatani watershed case then illustrates the full range of structural measures developed by Japanese engineering to reduce hydrological risks.